Characterization of collagen fibrils after equine suspensory ligament injury: An ultrastructural and biochemical approach. Issue 1 (April 2015) - Shikh Alsook, M.K.; Gabriel, A.; Salouci, M.; Piret, J.; Alzamel, N.; Moula, N.; Denoix, J.-M.; Antoine, N.; Baise, E.
Highlights: A biochemical and structural study of the equine SL after injury is reported. Purified fibrils of types I, III, and V collagens were analysed. Significant changes in types I, III and V collagen in damaged SL are recorded. These changes are highlighted for several months in injured tissue. Quantitative data and structural observations are highly related. Abstract: Suspensory ligament (SL) injuries are an important cause of lameness in horses. The mechanical properties of connective tissue in normal and pathological ligaments are mainly related to fibril morphology, as well as collagen content and types . The purpose of this study was to evaluate, using biochemical and ultrastructural approaches, the alterations in collagen fibrils after injury. Eight Warmblood horses with visible signs of injury in only one forelimb SL were selected and specimens were examined by transmission electron microscope (TEM). Collagen types I, III and V were purified by differential salt precipitation after collagen extraction with acetic acid containing pepsin. TEM revealed abnormal organization as well as alterations in the diameter and shape of fibrils after SL injury. The bands corresponding to types I, III and V collagen were assessed by densitometry after sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). Densitometric analysis indicated that the proportions of type III and type V collagen were higher ( P  < 0.001) in damaged tissues compared with normal tissues with a mean increase of 20.9% and 17.3%, respectively. Concurrently, a decrease ( P  < 0.001) in type I collagen within damaged tissues was recorded with a mean decrease of 15.2%. These alterations could be the hallmark of a decrease in the tissue quality and mechanical properties of the ligament. The findings provide new insight for subsequent research on tissue regeneration that may lead to the development of future treatment strategies for SL injury.